Purchase IntentionTowards Foreign Brands versus DomesticApparel Brands in Chennai - Suresh, Dr. M.; Deepa, Dr. V. (The journal of contemporary issues in business and government, 2021)
This study examines the differences between foreign brands and domestic brands in the Indian apparel market. Purchase Intention towards domestic and foreign apparel brand in the Indian market are examined. The purchase decision process into problem recognition, information search, alternative evaluation, purchase decision, and post-purchase behavior. Consumer decision making process is based on perceiving problems, searching for solutions, evaluating alternatives, and making decisions. Descriptive research design is followed in this research. Under non-probability sampling technique, convenience sampling method was used to select the respondent from population. The data were collected through questionnaire method. Sum of 552 Respondents met at the time of purchase in specified mall (Forum Vijaya mall and Express avenue mall), in Chennai City during their leisure time, with a request to fill in the questionnaire. This study finds that Indian consumers who fall in the age group of 40-49 have purchase intention towards European brands followed by American brand and Indian brand and also found that the respondents who fall in the Income of Rs. 40,000 to 60,000 have Purchase Intention European brand followed by American brand and Indian brand.